Comparing mean healing time of low fistula in Ano treated by Fistulotomy v/s Fistulectomy. - Usra Parvez; Salman Faridi (International Journal of Endorsing Health Science Research, 2021)
Background:Fistula in ano is a chronic abnormality usually lined by some degree of granulated tissue that runs outward from the anorectallumen, from internal to an external opening on perineum skin or buttock. The current study aimed to compare the mean healing time of low fistula in ano treated by fistulotomy v/s fistulectomy.Methodology:A randomized controlled trial was conducted at Liaquat National Hospital in Karachi-Pakistan, for six months after the approval of the synopsis by the CPSP. A total of 60 patients selected who met the inclusion criteria were enrolled in this study, with 30 patients in each group. Patients were divided into two groups randomly, i.e. Group-A: Fistula in Ano treated by Fistulotomy and Group-B Fistula in Ano treated by Fistulectomy. All the data was collected from the Department of General Surgery's inpatient services at Liaquat National Hospital, Karachi. The Patients were approached in clinics weekly until complete epithelization of the wound.Results:The overall mean age of patients was 41.83 ± 4.07years. In Group A (Fistulotomy), the mean age was observed to be 39.83 ± 6.8, and in Group B (Fistulectomy), the mean age was 44.1±5.9. The mean duration of symptoms was observed to be 3.37 ± 0.81 weeks. Comparatively, the duration of symptoms was found to be statistically insignificant (p-value: 0.511). Whereas the mean healing time was found to be highly significant between the two groups. (P-value: 0.000).Conclusion:It is concluded from the study results that there is a highly significant difference in terms of wound healing between fistulotomy and fistulectomy in fistula in ano treatment. Fistulotomyoffers an earlier wound healing as compared to fistulectomy.